HIV-Associated Tuberculosis in the Newborn and Young Infant - M. Adhikari; P. Jeena; R. Bobat; M. Archary; K. Naidoo; A. Coutsoudis; R. Singh; N. Nair (Hindawi Limited, 2011)
Each year, approximately 250 000 women die during pregnancy, delivery, or postpartum. Maternal mortality rates due to tuberculosis (TB) and HIV in Sub-Saharan Africa now supersede obstetric-related causes of mortality. The majority of cases occur in population-dense regions of Africa and Asia where TB is endemic. The vertical transmission rate of tuberculosis is 15%, the overall vertical transmission rate of HIV in resource-limited settings with mono- or dual-ARV therapy varies from 1.9% to 10.7%. If the millennium development goals are to be achieved, both HIV and TB must be prevented. The essential aspect of TB prevention and detection in the newborn is the maternal history and a positive HIV status in the mother. Perinatal outcomes are guarded even with treatment of both diseases. Exclusive breast feeding is recommended. The community and social impact are crippling. The social issues aggravate the prognosis of these two diseases.